Ventaja competitiva de la industria del dulce regional: estudio comparativo de empresas morelianas - Portales Gómez, Hilda (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
In Morelia one of the principal economic activities is the production of regional sweets that are considered to be a part of the culture of these city and that during the last years its participation has increased considerably not only on local markets, but on external markets also, where these products are received well. The industry of Morelia's sweet has presented increase in its income owed between other reasons to the increase of tourism in the state and for the high concentrations of immigrants from Michoacan in the United States, principal market puts of these products. In this investigation an analysis is realized on the similarities of the companies that shape this industry principally in the System of Management of the Quality and in the treatment of the same one, as well as in the sources of advantage that allow the companies to be competitive; thinking that the companies in general have similarities in the treatment of the quality and its principal source of competitive advantage: the products that are elaborated and the process of packing with the one that they are made; likewise there is described the chain of value of this industry for the best understanding of the importance of this economic activity of Morelia city. With the previous analysis the offer is elaborated to promote the competitiveness of the companies and to protect the principal sources of advantage that they possess to improve the income of the businessmen and to support this tradition as part of the culture of Morelia City.

En Morelia una de las principales actividades económicas es la producción de dulces regionales que son considerados como parte de la cultura de esta ciudad y que durante los últimos años ha aumentado considerablemente su participación no solo en mercados locales, sino en mercados externos también, en los que estos productos son bien recibidos. La industria del dulce de Morelia ha presentado aumento en sus ingresos debido entre otras causas al aumento de turismo en el estado y por las altas concentraciones de migrantes michoacanos en Estados Unidos, principal mercado meta de estos productos. En esta investigación se realiza un análisis sobre las similitudes de las empresas que conforman esta industria principalmente en los Sistemas de Gestión de la Calidad y en el tratamiento de la misma, así como en las fuentes de ventaja que permiten a las empresas ser competitivas; encontrándose que las empresas en general tienen similitudes en el tratamiento de la calidad y su principal fuente de ventaja competitiva son los productos que se elaboran y el proceso de empaque con el que son fabricados. Así mismo se describe la cadena de valor de esta industria para el mejor entendimiento de la importancia de esta actividad económica de la ciudad de Morelia. Con el análisis anterior se elabora la propuesta para promover la competitividad de las empresas y proteger las principales fuentes de ventaja que poseen para mejorar los ingresos de los empresarios y mantener esta tradición como parte de la cultura Moreliana.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2009-0008; Industria dulcera; Comercio internacional; Variables; Calidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/930